The herbalmedicine with nondirect antibacterial action in the complex therapy of patients with odonthogenic flegmons - M Sh Mustafaev; Z F Kharaeva; B A Rekhviashvili; O M Gendugova (RUDN Journal of Medicine, 2009)
The investigation of the clinical effectiveness of the complex treatment with BioReks was done. This therapy leads to more fast elimination of the main inflammations markers and to more effective reparation. The good effect of the BioReks connects with decreasing of defence of inflectional agents to bactericidal actions of neutrophils and antioxidant properties if medicine.